Change in Cerebral Perfusion after Carotid Angioplasty with Stenting Is Related to Cerebral Vasoreactivity: A Study Using Dynamic Susceptibility-Weighted Contrast-Enhanced MR Imaging and Functional MR Imaging with a Breath-Holding Paradigm - Chang, T.-Y; Liu, H.-L; Lee, T.-H; Kuan, W.-C; Chang, C.-H; Wu, H.-C; Wu, T.-C; Chang, Y.-J (American journal of neuroradiology : AJNR, 2009)
Carotid angioplasty with stent placement (CAS) is an optional treatment for significant carotid stenosis. Cerebral vasoreactivity (CVR), representing the reserve capacity of cerebral perfusion, usually decreases in patients with severe carotid stenosis. This study aimed to investigate the relationship between the baseline CVR assessed by functional MR imaging (fMRI) and the changes in cerebral blood flow (CBF) after CAS. Fourteen patients with at least 70% unilateral carotid stenosis underwent CAS. Baseline CVR was evaluated by fMRI a under breath-holding paradigm. CBF was assessed by dynamic susceptibility-weighted contrast-enhanced MR imaging before and 3-5 days after CAS. The lateral index (LI) was defined as (n - L) / (n + L), where n and L represent the number of activated voxels in fMRI on the normal and lesion hemispheres, respectively. No subject had clinical evidence of hyperperfusion syndrome. The LI represented baseline CVR. Patients were divided into normal (LI < 0, n = 6) and impaired (LI > 0, n = 8) CVR groups. The CBF on the normal and lesion sides was calculated separately. CBF increment on the lesion side after CAS was significantly higher in the impaired CVR group than that in the normal CVR group (P = .035). There was a significantly positive correlation between CVR impairment and the CBF increment (P = .026). fMRI could be a reproducible tool in evaluating CVR. After CAS, early CBF changes on the lesion side are more prominent in patients with impaired CVR. Baseline CVR might predict early CBF increase after CAS.